Saturated and unsaturated triglyceride-enriched diets modify amino acid content in the mice hippocampus. (10th January 2023) - Fernández-Felipe, Jesús; Sanz-Martos, Ana B.; Marcos, Alberto; Lorenzo, María P.; Cano, Victoria; Merino, Beatriz; Ambrosio, Emilio; Del Olmo, Nuria; Ruiz-Gayo, Mariano
Graphical abstract: Highlights: Saturated (SOLF) and unsaturated high-fat diets (UOLF) trigger changes in amino acid content in the hippocampus. SOLF and UOLF increase l -glutamate and l -aspartate levels, while SOLF specifically reduces GABA. UOLF decreases d -serine. In vitro palmitic and oleic acids partially reproduce the effect of SOLF and UOLF. The effect of high-fat diets on hippocampus neurotransmission may be related to the effect of oleic and palmitic acids on HIP amino acid content. Abstract: Elevated intake of fat modulates l -glutamate (l -Glu) turnover within the hippocampus (HIP). Our aim has been to investigate the effect of saturated vs unsaturated fat on the content of l -Glu and other amino acids involved in synaptic transmission within the HIP. The study was carried out in male mice fed (2 h or 8 weeks) with standard chow or with diets enriched either with saturated (SOLF) or unsaturated triglycerides (UOLF). An in vitro assay was performed in HIP slices incubated with palmitic (PA), oleic (OA), or lauric acid (LA). Amino acids were quantified by capillary electrophoresis. While both diets increased the amount of l -Glu and l -aspartate and decreased l -glutamine levels, only UOLF affected d -serine and taurine levels. γ-Aminobutyric acid was specifically decreased by SOLF. In vitro assays revealed that PA and OA modified l -Glu, glycine, l -serine and d -serine concentration. Our results suggest that fatty acids contained in SOLF and UOLF have an impact on HIP amino acid turnover that may account, at least partially, for the functional changes evoked by these diets.